Analisis Konten Promosi Instagram Starsbox Barbershop Kota Batam - Pertiwi, Siska Putri; Rorong, Michael Jibrael (LPPM Universitas Putera Batam, 2022)
Instagram is an image-based social media that provides online photo or video sharingservices. Starsbox Barbershop is a service business that was established on July 6 2015which has 8 branches in the city of Batam. Starsbox barbershop has an existence in theeyes of the public where the company has been around for a long time. , not only providingservices but also producing its own pomade brand to sell and only market it at starsboxbarbershop outlets. Starsbox Barbershop utilizes social media Instagram with the account@Strasboxbarbershop_batam with 13.6 thousand followers as a promotional medium withcontent in the form of photos and videos. In promotional activities, of course, look at whatcontent will be conveyed to the public, apart from content, there is language which is oneof the values in the promotion. This study aims to analyze and describe the meanings andsigns in Strasbox Barbershop Promotional Content. Promotional content is not just aboutcommunicating through promotions but focuses on how the meaning gets clear to theaudience. The author uses a qualitative research method with a Sanders Pirece semioticanalysis approach. The results of this study are to examine the sign, implementation andcolor of the content made in the form of photos and videos that are presented throughphotos and Scene – Scene scenes in the promotional content videos so that they attractthe interest of the audience.